Incorporating Virtual Reality in Public Health Campaigns: COVID-19 as the Context - Xu, Zhan; Weser, Veronica; Peng, Lulu; Laffidy, Mary (Social science computer review, 2024)
One of the greatest challenges for public health campaigns is communicating health risks due to the existence of psychological distance. Using COVID-19 as a context, this study designed and tested virtual reality (VR) campaigns based on construal level theory. It assessed the immediate and after-effects of VR on COVID-19 preventive intentions/behaviors and risk perceptions. A total of 120 participants were randomly assigned to see one of four messages: a VR message emphasizing self-interest, a VR message emphasizing other-interest, a print message emphasizing self-interest, or a print message emphasizing other-interest. Preventive intentions/behaviors were assessed at three different times: before, immediately after, and one week after the experimental treatment. Immediately following message exposure, participants exposed to the VR messages perceived a higher level of self-risk than those exposed to print messages. Disgust and fear mediated these effects. One week following message exposure, unvaccinated participants exposed to the VR messages had a higher intention to get vaccinated than those exposed to print messages. Recommendations on how to effectively utilize VR in health interventions are provided.